2010
DOI: 10.1186/1471-2148-10-193
|View full text |Cite
|
Sign up to set email alerts
|

Filoviruses are ancient and integrated into mammalian genomes

Abstract: BackgroundHemorrhagic diseases from Ebolavirus and Marburgvirus (Filoviridae) infections can be dangerous to humans because of high fatality rates and a lack of effective treatments or vaccine. Although there is evidence that wild mammals are infected by filoviruses, the biology of host-filovirus systems is notoriously poorly understood. Specifically, identifying potential reservoir species with the expected long-term coevolutionary history of filovirus infections has been intractable. Integrated elements of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(163 citation statements)
references
References 44 publications
(58 reference statements)
5
155
0
3
Order By: Relevance
“…5), which is about the time the Earth emerged from the last ice age. Our estimate is similar to a previous calculation (7,100 to 7,900 years) based on synonymous and nonsynonymous substitution ratios (25) and far younger than other recent assessments using non-clock-based methods that rely on the assumption of filovirus-like elements that appear to have been integrated into the genome of a variety of mammals and subjected to different evolutionary pressures (27,28). Additional approximations of MRCA that resulted in older estimates than those generated in this study differed in terms of more-limited numbers of whole-genome taxa as well as methodology (4,26).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…5), which is about the time the Earth emerged from the last ice age. Our estimate is similar to a previous calculation (7,100 to 7,900 years) based on synonymous and nonsynonymous substitution ratios (25) and far younger than other recent assessments using non-clock-based methods that rely on the assumption of filovirus-like elements that appear to have been integrated into the genome of a variety of mammals and subjected to different evolutionary pressures (27,28). Additional approximations of MRCA that resulted in older estimates than those generated in this study differed in terms of more-limited numbers of whole-genome taxa as well as methodology (4,26).…”
Section: Resultssupporting
confidence: 77%
“…Although the filoviruses are thought to have originated quite some time ago, age estimates have ranged from a few thousand (25,26) to hundreds of thousands (4) to a few million (27,28) years ago. Further confusing the issue, some authors have presented data indicating that viruses of at least one filovirus species (Zaire ebolavirus) share a most recent common ancestor (MRCA) in the very recent past (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…After analysis using Decision Tree, trying 9, 13, and 17 windows of analysis, we thoroughly investigated genetic structure of Bundibugyo Ebolavirus, Reston Ebolavirus, Sudan Ebolavirus, TaiForest Ebolavirus, and Zaire Ebolavirus. [15] As a result of analysis, we found that high windows shows more detailed information about DNA sequences of Ebolaviruses and there are similarities of DNA sequences between the species of it. Since Reston Ebolavirus does not cause vital disease to humans as it does to animals such as pigs and monkeys, we look forward to finding the ways of curing Ebolavirus disease [16].…”
Section: Discussionmentioning
confidence: 93%
“…For example, EVE discovery can expand the past and current known host range of viral families [7][8][9], contribute to the characterization of the viral flora infecting a specific organism or lineage [10,11] and help to identify reservoir species and/or reconstruct complex transmission routes of zoonotic viruses [12][13][14]. Furthermore, endogenization events can be dated and used to calibrate long-term evolutionary patterns of modern virus families [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%